First Reported Case of Gabriele-de Vries Syndrome with Spinal Dysraphism - Nenad Koruga; Silvija Pušeljić; Marko Babić; Mario Ćuk; Andrea Cvitković Roić; Vjenceslav Vrtarić; Anamarija Soldo Koruga; Alen Rončević; Višnja Tomac; Tatjana Rotim; Tajana Turk; Domagoj Kretić; et al. (MDPI AG, 2023)
Gabriele-de Vries syndrome is a rare autosomal dominant genetic disease caused by de novo pathogenic variants in the Yin Yang 1 (YY1) gene. Individuals with this syndrome present with multiple congenital anomalies, as well as a delay in development and intellectual disability. Herein, we report the case of a newborn male patient with a novel de novo pathogenic variant in the Guanine Nucleotide-Binding Protein, Alpha Stimulating (GNAS) gene, which was identified by whole-exome sequencing. Our patient suffered from a large open spinal dysraphism which was treated surgically immediately after birth. During the follow-up, facial dysmorphism, bladder and bowel incontinence, and mildly delayed motor and speech development were observed. Congenital central nervous system disorders were also confirmed radiologically. In this case report, we present our diagnostic and treatment approaches to this patient. To our knowledge, this is the first reported case of Gabriele-de Vries syndrome presenting with spinal dysraphism. Extensive genetic evaluation is the cornerstone in treatment of patients with suspected Gabriele-de Vries syndrome. However, in cases with potentially life-threatening conditions, surgery should be strongly considered.